A novel NLRP3 inhibitor as a therapeutic agent against monosodium urate-induced gout - Park, Kihyoun; Shin, Injae; Kim, Yoonseon; Kang, Hyereen; Oh, Soo-Jin; Jang, Eunkyeong; Sim, Taebo; Youn, Jeehee; Lee, Myung-Shik (Frontiers in Immunology, 2024)
NEK7 is a critical component in NLRP3 inflammasome activation, mediating NLRP3 oligomerization. We developed an inhibitor of NEK7, SLC3037, and studied its effect on monosodium urate (MSU)-induced gout. SLC3037 inhibited inflammasome activation in vitro by MSU and other inflammasome activators through blockade of NLRP3 binding to NEK7 or oligomerization, and subsequent ASC oligomerization/phosphorylation. SLC3037 significantly ameliorated foot pad swelling and inflammation by MSU injection. SLC3037 also significantly attenuated inflammasome activation in vivo as evidenced by decreased IL-1 content and reduced IL-1 maturation in foot pad tissue. Effects of SLC3037 were superior to those of colchicine, a firstline drug against gouty attack, because reduction of foot pad swelling and inflammasome activation in vivo by SLC3037 was more pronounced compared to colchicine. There was no significant adverse effect associated with SLC3037 administration in hemogram, blood chemistry or major organ biopsy.Particularly, SLC3037 did not cause reduction of the number and height of intestinal villi, while such adverse effects were observed after colchicine administration. SLC3037, a NLRP3 inhibitor blocking NEK7 binding to NLRP3, could be a novel agent against diseases associated with NLRP3 inflammasome activation such as gout, cardiovascular diseases, metabolic syndrome or neurodegenerative diseases.